It’s not in my head: a qualitative analysis of experiences of discrimination in people with mental health and substance use conditions seeking physical healthcare - Cunningham, Ruth; Imlach, Fiona; Haitana, Tracy; Every-Palmer, Susanna; Lacey, Cameron; Lockett, Helen; Peterson, Debbie (Frontiers in Psychiatry, 2023)
Introduction Clinician bias contributes to lower quality healthcare and poorer health outcomes in people with mental health and substance use conditions (MHSUC). Discrimination can lead to physical conditions being overlooked (diagnostic overshadowing) or substandard treatment being offered to people with MHSUC. This research aimed to utilise experiences of people with MHSUC to identify discrimination by clinicians, including the role of clinician’s beliefs and assumptions in physical health service provision. Methods We surveyed people with MHSUC who accessed physical healthcare services. Of 354 eligible participants, 253 responded to open-ended questions about experiences of those services. Thematic descriptive analysis of survey responses was completed using existing stigma frameworks and inductive coding. Results One dominant theme from survey responses was that diagnostic overshadowing by clinicians was driven by clinician mistrust. Another theme was that clinicians assumed respondent’s physical symptoms, including pain, were caused by MHSUC. This influenced decisions not to initiate investigations or treatment. Respondents perceived that clinicians focused on mental health over physical health, contributing to suboptimal care. Discussion Discrimination based on MHSUC leads to poor quality care. Health systems and clinicians need to focus quality improvement processes on access to and delivery of equitable physical healthcare to people with MHSUC, address stereotypes about people with MHSUC and improve integration of mental and physical healthcare.